1989
DOI: 10.1038/bjc.1989.102
|View full text |Cite
|
Sign up to set email alerts
|

The origin and nature of stromal osteoclast-like multinucleated giant cells in breast carcinoma: implications for tumour osteolysis and macrophage biology

Abstract: (Fry, 1927;Agnantis & Rosen, 1978;Factor et al., 1977;Holland & van Haelst, 1984;Nielsen & Kiaer, 1985;Tavassoli & Norris, 1986) and tumours in other extraskeletal sites (Andreev et al., 1964;Dorney, 1967;Nishiyama et al., 1972; EshunWilson, 1973;Balogh et al., 1985; Berendt et al., 1985). The origin and nature of these cells and their relationship to osteoclasts and macrophage polykaryons is unknown. They are present in the tumour stroma and are generally thought to represent part of the host reponse to the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(44 citation statements)
references
References 40 publications
(26 reference statements)
1
42
1
Order By: Relevance
“…In this way, giant cells derived from a giant cell reparative granuloma of the jaw (Flanagan & Chambers, 1988) and giant cells from a giant cell rich malignant fibrous histiocytoma (Flanagan & Chambers, 1989) were considered to be osteoclasts. However, it has recently been shown that tumour-associated macrophage polykaryons derived from a primary breast carcinoma are also able to resorb bone (Athanasou et al, 1989). This result appeared inconsistent with the general belief that no polykaron other than an osteoclast is capable of bone resorption (Chambers & Horton, 1984).…”
contrasting
confidence: 55%
See 1 more Smart Citation
“…In this way, giant cells derived from a giant cell reparative granuloma of the jaw (Flanagan & Chambers, 1988) and giant cells from a giant cell rich malignant fibrous histiocytoma (Flanagan & Chambers, 1989) were considered to be osteoclasts. However, it has recently been shown that tumour-associated macrophage polykaryons derived from a primary breast carcinoma are also able to resorb bone (Athanasou et al, 1989). This result appeared inconsistent with the general belief that no polykaron other than an osteoclast is capable of bone resorption (Chambers & Horton, 1984).…”
contrasting
confidence: 55%
“…This pattern of bone resorption is completely different from that of rodent osteoclasts or the osteoclast-like giant cells of a giant cell tumour of bone , both of which produce numerous resorption pits on bone slices. Moreover, although a few large resorption areas were seen, the resorption pits produced by GCTTS and tumour-associated giant cells were generally smaller than those associated with osteoclasts as well as fewer in number (Flanagan & Chambers, 1988;Flanagan & Chambers, 1989;Athanasou et al, 1989). In addition, cells isolated from the GCTTS produced poorly defined areas of surface roughening, a type of bone degradation which has previously been noted to be an uncommon form of osteoclastic bone resorption .…”
Section: Discussionmentioning
confidence: 93%
“…Extensive low-grade surface resorption by the numerous mononuclear phagocytes isolated in these studies may be the functional and morphological correlate of this phenomenon. We have previously shown that macrophages and macrophage polykaryons isolated from extraskeletal tumours containing large numbers of these cells are also capable of bone resorption (Athanasou et al, 1989;Athanasou, 1991b); such resorption is similar in type to that described in this study with formation of a few resorption pits and extensive lowgrade surface resorption.…”
Section: Discussionsupporting
confidence: 73%
“…TAM or AM-containing cell suspensions in alpha minimal essential medium plus 10% foetal calf serum (Gibco) (MEM/FCS) were added to 6mm wells (500cells/well) containing either bone slices or glass coverslips, half of which had been seeded (1,000 cells/well) 24 h earlier with the mouse marrow stromal cell line ST2 (Riken cell bank, Japan) (Athanasou et al, 1989). Four bone slices (half previously seeded with ST2 cells) were studied for each variable, and cell cultures were incubated at 37°C (5% CO2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation